2013
DOI: 10.3184/095422913x13785624164620
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of heavy metals in the geochemical phases of sediments from the Tietê River, Brazil

Abstract: The fractionation of heavy metals in riverbed sediments along the Tietê River basin, a highly polluted river in southeast region of Brazil, was investigated using a four-step sequential extraction procedure, in order to determine the concentration and distribution of Cu, Co, Cr, Cd, Zn, Ni and Pb, in the river bottom sediments, related to the potential mobility of geochemical phases. Around the metropolitan area of the City of São Paulo, which has 25 million people, the pollution is associated with municipal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…In France, in the region adjoining the Gironde, once operated a zinc deposit, which is the cause of such contents of this element (Larrose et al, 2010). Relatively to the rest three rivers, no pronounced zinc pollution sources are identified either (Larrose et al, 2010) (Skorbiłowicz et al, 2016)(Da Silva et al, 2019) (Mortatti et al, 2013).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…In France, in the region adjoining the Gironde, once operated a zinc deposit, which is the cause of such contents of this element (Larrose et al, 2010). Relatively to the rest three rivers, no pronounced zinc pollution sources are identified either (Larrose et al, 2010) (Skorbiłowicz et al, 2016)(Da Silva et al, 2019) (Mortatti et al, 2013).…”
Section: 2mentioning
confidence: 99%
“…The significant mean contents of chromium in the Hrazdan (181mg/kg) can be explained by untreated urban domestic runoffs which empty into the river on the sampling site. By this index, the Hrazdan is similar to the Tiete River in Brazil, which besides urban domestic waters receives chromium-containing agricultural wastewater as well, and the Fan River in Albania, one of the sections of which accommodates a copper deposit and copper smeltery (Mortatti et al, 2013)(X.Kumanova, 2012.…”
Section: 2mentioning
confidence: 99%
“…Sany et al (2013) studied the distribution of heavy metal in the coastal sediments of Port Klang, Selangor, Malaysia.Their results showed that the concentrations of some metals, such as As, Cd and Pb were comparatively higher than the background values Mortatti et al (2013). studied the distribution of heavy metals (Cu, Co, Cr, Cd, Zn, Ni and Pb) in the geochemical phases of sediments from the Tietê River, Brazil.…”
mentioning
confidence: 99%
“…Therefore the determination of total metal concentration alone is not adequate to evaluate the possible health risk of metals because it only gives limited information (Tessier et al, 1979;Kalis et al, 2007;Ogubanjo et al, 2015). The best way to predict these geochemical forms of the metals in the soil is to apply sequential extraction procedure which will reveal the fate, toxicity and the environmental impact of the metals in the soils (Mortatti et al, 2013). Many sequential extraction schemes have been reported in literature and studies have shown that all of them generally have some disadvantages (Davison et al, 1999, Ahmadipour, et al, 2014.…”
Section: Introductionmentioning
confidence: 99%